Understanding modern warfare - Jordan, David (David John); Kiras, James; Lonsdale, David J.; Speller, Ian 1969-; Tuck, Christopher; Walton, C. Dale 1971- (Cambridge Cambridge University Press, 2016)
Understanding Modern Warfare has established itself as the leading introduction to the issues, ideas, concepts and context necessary to understand the theory and conduct of warfare in the twentieth and twenty-first centuries. It is an invaluable text for military professionals and students of military history. Key features include: incisive coverage of the debates surrounding contemporary and future warfare; accessible, yet sophisticated, discussion across the land, sea, and air environments; and coverage of contemporary topics such as drones, cyber warfare, and hybrid warfare. The book makes extensive use of text boxes to explain key concepts and to reference extended examples, and it includes annotated guides to further reading and key questions to promote the reader's further thinking. This second edition has been fully revised and updated to take into account new debates and recent events in Syria, Iraq and Ukraine, and it has also been restructured to further improve its usefulness as a teaching tool.
Includes bibliographical references and index.
Keywords: Military art and science -- History -- 20th century; Military art and science -- History -- 21st century; Military history, Modern -- 20th century; Military history, Modern -- 21st century